La historia de la teoría electroquímica y su contribución a la promoción de la explicación científica en la química escolar - Camacho González, Johanna (Revista Científica, 2012)
This research presents the main findings regarding how are scientific explanations about the theory Electrochemistry in High School? The research is based on the current need to promote the scientific explanation as a scientific competence and the use of history of science as an area metascientific that can contributing positively to this need. This study was conducted in Santiago de Chile through a collective case study, which was evident two different sequences for the construction of explanations through the teaching of the electrochemical theory.